Celestial Suite: uma Ferramenta para a Tradução e Execução de Código de Três Endereços - Galante, Guilherme; Boll, Daniel Carlos Chaves (International Journal of Computer Architecture Education, 2024)
The article describes the development and evaluation of a didactic tool called Celestial Suite, designed for teaching compilers. The tool converts programs described in three-address code into MIPS assembly, in addition to allowing emulation and execution through a virtual machine. Student feedback indicated that the tool is effective as an educational resource but suggested improvements, such as more accurate error messages, editor tips, and better documentation.